Attribution of Conduct in UN Peacekeeping Operations - Perisic, Petra (Pécs journal of international and European law, 2020)
This paper explores the rules on attribution of conduct within United Nations (UN) peacekeeping operations. Altough there is now a prevaiiling judical practice of employing the effective control test, the content of this test is not sufficiently clear. A review of the so-far scare judicial practice demonstrates that different courts interpret the test in different ways. This leads to uncertainty on how to apply the effective control test in future cases, the number of which will undoubtedly incraese, as the number of peacekeeping operations in the world rises. In this paper, several judicial decisions dealing with the issue of attribution in the context of peacekeeping operations are analyzed and compared. The conclsuion highlights some of the essentail flaws of the current system, which should be dealt with in order to achieve a more unified approach to tackling the attribution issue.